2018
DOI: 10.1108/jidob-06-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The contributory role of autism symptomology in child pornography offending: why there is an urgent need for empirical research in this area

Abstract: Ti t l e Th e c o n t ri b u t o ry r ol e of a u tis m sy m p t o m olo gy in c hil d p o r n o g r a p hy offe n di n g :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 108 publications
(179 reference statements)
0
17
0
Order By: Relevance
“…Currently, the understanding of the association between ASD and engaging in viewing of IIOC is poorly recognised and understood both by the general public as well as clinical and legal professionals. The importance of addressing this has been recently raised (Dubin & Horowitz, 2017;Allely & Dubin, 2018;Allely, Kennedy, & Warren, 2019). The case presented here stresses the importance of early recognition and diagnosis of ASD in order to receive a fair trial (see also .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the understanding of the association between ASD and engaging in viewing of IIOC is poorly recognised and understood both by the general public as well as clinical and legal professionals. The importance of addressing this has been recently raised (Dubin & Horowitz, 2017;Allely & Dubin, 2018;Allely, Kennedy, & Warren, 2019). The case presented here stresses the importance of early recognition and diagnosis of ASD in order to receive a fair trial (see also .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that they more often access the media and pornography in an attempt to gain information about sex. This can often lead to unintentional online offending in some cases (see Allely & Dubin, 2018). Many individuals with ASD have insight into their own impairments in relation to romantic relationships which has an adverse impact on their social relationships (Stokes, Newton, & Kaur, 2007;Brown-Lavoie, Viecili, & Weiss, 2014; Barnett & Maticka-Tyndale, 2015;Parchomiuk, 2018 In a survey with individuals with ASD and typically developing individuals, Mehzabin and Stokes (2011) found that individuals with ASD have less adaptive sexual knowledge and behaviours, reported less social behaviour (e.g., going out with friends), less education about sex and sexuality and less sexual experience (Mehzabin & Stokes, 2011).…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Most people with autism receive information about sex on the internet, television and pornography compared to parents, friends and teachers following the stigma of community on sexual issues (Curtis 2017) as well as being difficult to interact with their peers (Allely & Dubin, 2018). The portrayal of sexuality and intimacy from such sources may not be appropriate (Higgs & Carter 2015), but it is possible that the information absorbed by individuals with autism about sex is completely misleading (Beddows & Brooks 2016).…”
Section: Pornographymentioning
confidence: 99%
“…The portrayal of sexuality and intimacy from such sources may not be appropriate (Higgs & Carter 2015), but it is possible that the information absorbed by individuals with autism about sex is completely misleading (Beddows & Brooks 2016). For example, individuals with autism who watch child pornography on the internet are less likely to understand that sexual activity with children is criminal (Allely & Dubin, 2018) thus attempt to practice such sexual activity with children (Ray et al, 2004). The involvement of individuals with autism with child sexual abuse dragged the individual into more dangerous situations due to charges against the child would result in more severe penalties.…”
Section: Pornographymentioning
confidence: 99%